3x+3=2(6x-2)+7

Simple and best practice solution for 3x+3=2(6x-2)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+3=2(6x-2)+7 equation:


Simplifying
3x + 3 = 2(6x + -2) + 7

Reorder the terms:
3 + 3x = 2(6x + -2) + 7

Reorder the terms:
3 + 3x = 2(-2 + 6x) + 7
3 + 3x = (-2 * 2 + 6x * 2) + 7
3 + 3x = (-4 + 12x) + 7

Reorder the terms:
3 + 3x = -4 + 7 + 12x

Combine like terms: -4 + 7 = 3
3 + 3x = 3 + 12x

Add '-3' to each side of the equation.
3 + -3 + 3x = 3 + -3 + 12x

Combine like terms: 3 + -3 = 0
0 + 3x = 3 + -3 + 12x
3x = 3 + -3 + 12x

Combine like terms: 3 + -3 = 0
3x = 0 + 12x
3x = 12x

Solving
3x = 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
3x + -12x = 12x + -12x

Combine like terms: 3x + -12x = -9x
-9x = 12x + -12x

Combine like terms: 12x + -12x = 0
-9x = 0

Divide each side by '-9'.
x = 0

Simplifying
x = 0

See similar equations:

| 4x-13=2x+4 | | -13x-18=1 | | (x+2.9)-(0.3x+4)=9 | | x+10=15-8 | | .25(X+3)=8X-11(1-X)-7 | | 4x+-13=2x+4 | | 6t+8=14+3d | | 312x+800=706-350x | | .5(x+2)=3x-5(3-x)-8 | | -72+6v=-4 | | .4(4x+11)=4(1-3x)+14 | | -3/2v-4/7=-8/5 | | 2x-5+6-x-2x=17 | | 150+2p=195-1p | | (-3)+17x-6(-3)=2 | | 3(4x-5)=5(2x-1) | | x=-14+5y | | 5-x+37=50-10 | | 3a+6=-4a+2 | | 12x-21=28(4x-1) | | 12y^9/2y^11 | | 5-9/8x=6 | | X-4+4=-7 | | (y^2-x^2)dy+(2*x*y)dx=0 | | X-4+4=7 | | F(x)=-3(x+3)squared+3 | | 4+16x=10+15x | | 8x+-7=-2x+5 | | 10+3x-x-4=x | | 13x+17+34=90 | | 8x+1+9x-7=180 | | Z-6=z-4 |

Equations solver categories